Effect of PHF-1 hyperphosphorylation on the seeding activity of C-terminal Tau fragments - Léa El Hajjar; Emmanuelle Boll; François-Xavier Cantrelle; Clarisse Bridot; Isabelle Landrieu; Caroline Smet-Nocca (Scientific Reports)
Abstract Tau proteins as neurofibrillary tangles are one of the molecular hallmarks of Alzheimer’s disease (AD) and play a central role in tauopathies, a group of age-related neurodegenerative disorders. The filament cores from diverse tauopathies share a common region of tau consisting of the R3-R4 microtubule-binding repeats and part of the C-terminal domain, but present a structural polymorphism. Unlike the fibril structure, the PTM signature of tau found in neuronal inclusions, more particularly hyperphosphorylation, is variable between individuals with the same tauopathy, giving rise to diverse strains with different seeding properties that could modulate the aggressiveness of tau pathology. Here, we investigate the conformation, function and seeding activity of two tau fragments and their GSK3β-phosphorylated variants. The R2Ct and R3Ct fragments encompass the aggregation-prone region of tau starting at the R2 and R3 repeats, respectively, and the full C-terminal domain including the PHF-1 epitope (S396, S400, S404), which undergoes a triple phosphorylation upon GSK3β activity. We found that the R3Ct fragment shows both a greater loss of function and pathological activity in seeding of aggregation than the R2Ct fragment which imposes a cross-seeding barrier. PHF-1 hyperphosphorylation induces a local conformational change with a propensity to adopt a β-sheet conformation in the region spanning residues 392–402, and exacerbates the seeding ability of fragments to induce aggregation by overcoming a cross-seeding barrier between tau variants.